THE ANALYSIS OF HIGH FREQUENCY WORD ON ENGLISH WRITTEN MODULES IN STATE ISLAMIC COLLEGE JURAI SIWO METRO - ARIANSYAH, DANI (Department of English Education of STAIN Jurai Siwo Metro, 2014)
The problem of the writer had outlined in this paper deals with vocabularies which are frequently used in written language, in technical term, they are called High Frequency Word (HFW). The primary goal of this research was to figure out HFW provided in the English written modules produced by the lecturers of State Islamic College Jurai Siwo Metro. The writer took five modules written by five different lecturers as his purposive sample. A qualitative descriptive was used to approach the data. The researcher collected the data by observation and documentation. Meanwhile, Creswellâs generic steps model was used to analyze the data. The result of analysis illustrates that there are 145 High Frequency Word found on those five modules. It can be classified by the word classes namely 31% adjective, 23% noun, 23% verb, 23% adverb. In conclusion, there are several HFW in the English written modules that are used in the State Islamic College Jurai Siwo Metro